Análise das propriedades fotodinâmicas de ftalocianinas de gálio e índio livres e encapsuladas em nanopartículas de PHB - Vasconcelos, Vannyla Viktória Viana (2021)
The photodynamic therapy is promoted by a chemical reaction activated by light, with wavelength in the red region involving a photosensitizer (FS) a light source and molecular oxygen. This therapy is promising, however, some challenges hinder the excellence of this process, such as the targeting of the active compound, its permeability, bioavailability and the control of the synthetic process of carrier systems used to encapsulate the FS. Thus, this work evaluated the ability of gallium and indium (hydroxyphenylpropanone)-phthalocyanine free and encapsulated in polyhydroxybutyrate (PHB) nanoparticles (NPs) to act as FS in photodynamic therapy (PDT). The central atom bound to the phthalocyanines (Ga or In), the percentage of ethanol in the aqueous phase and the molar mass of polyvinyl alcohol (PVA) (kDa) were evaluated on the size, encapsulation and recovery efficiency of the NPs. The nanoparticles were also characterized morphologically. The formulations with nanoparticulate properties best suited for DFT application. Photooxidation assays of biomolecules using bovine serum albumin (BSA) and tryptophan (Trp), molecular docking calculations were also performed to evaluate the interaction of FSs with the polymer matrix and with BSA. The increase in PVA molar mass and the change of the phthalocyanine-bonded central atom directly influenced the NP size, favoring the obtainment of particles with diameters smaller than 200nm. The photooxidation assays revealed that the encapsulated FS were more efficient than the free FS in photooxidizing the biomolecules, being the gallium phthalocyanine more efficient than the indium one. The results indicate that these substances are potential FSs for use in FTD, with gallium-containing phthalocyanine standing out.